The scope of LC-MS-based metabolomics - Koparir, Pelin; Baral, Inanç (Nova Science Publishers, Inc., 2023)
The field of metabolomics is becoming an indispensable part of clinical research with its potential for the discovery of biomarkers and diagnostic molecules along with its potential for revealing concealed aspaects of pathophysiological conditions. Basically, metabolomics aims to objectively identify and quantify all metabolites present in a living system at a particular state or point of time. In summary, all metabolomics research contains steps of sample collection and processing, detection, and analysis of raw data, and evaluation of the results. A frame of the metabolic state of a eukaryotic living system can be understood by using various biological samples ranging from cerebospinal fluid to tissues to blood plasma. Each biological sample contains a large set of endogenous compounds that are classified under various compounds, e.g., organic acids, amino acids, peptides, carbohydrates, etc. Both internal (gender, age, health, physiological state, etc.) and external (diet, lifestyle, pollution, environment, etc.) stimuli affect the metabolite composition, sometimes quite strikingly. A large number of variables are effective in the composition of metabolites, which requires a careful design of the research and the use of standardized experimental procedures encompassing all the steps. There are conventional standardized methods for the individual identification of particular metabolites based on their compound classes. Metabolomics methods, however, aim to detect and profile the global metabolite context by applying pattern recognition and profiling on complex sets of metabolite data. Currently, there is no single approach to achieve such a daunting task. Therefore, different analytical approaches are used according to the intended metabolomics study. An analytical method should be both sensitive and comprehensive to cover large data series of metabolites in a robust and specific manner. Of the available methods, nuclear magnetic resonance (NMR) and mass spectrometry are the best instrumental and analytical methods frequently used for metabolomics research. The high sensitivity and wide dynamic range provided by mass spectrometry (MS) can be coupled with chromatography methods to achieve large-scale analysis of metabolites from biological samples. Mass spectrometry can be coupled with liquid chromatography (LC) for the metabolite profiling of thermolabile or involatile compounds. The LC-MS-based metabolomics research that used the liquid chromatography-mass spectrometry (LC-MS) approach was reviewed in this chapter. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Lc; Liquid chromatography; Mass spectrometry; Metabolite; Metabolomics; Ms; Spectrometry